Comparison of activities of rifapentine and rifampin against Mycobacterium tuberculosis residing in human macrophages. - Mor, N (1995)
The activities of rifapentine and rifampin against Mycobacterium tuberculosis residing in human monocyte-derived macrophages were determined. The MICs and MBCs of rifapentine for intracellular bacteria were two- to fourfold lower than those of rifampin. For extracellular bacteria, this difference was less noticeable. Nevertheless, the more favorable pharmacokinetics of rifapentine over rifampin was addressed in other experimental models. These models showed substantial differences after short pulsed exposures of the infected macrophages to the drugs and when the infected macrophages were exposed to changing drug concentrations that imitated the pharmacokinetic curves observed in blood. Once-a-week exposures to rifapentine concentrations equivalent to those attained in blood after one 600-mg dose resulted during the first week in a dramatic decline in the number of bacteria, and this decline was maintained at a minimal level for a period of four weeks. The results of this study have shown the suitability of rifapentine for intermittent-treatment regimens. The prolonged effect of rifapentine found in this study may be associated with high ratios of intracellular accumulation, which were four- to fivefold higher than those found for rifampin. Further studies on the intracellular distribution of rifamycins and on the sites of actual interaction between the drugs and bacteria residing in macrophages are necessary.